High-sensitive Troponin T measurements early after heart transplantation predict short- and long-term survival - Erbel, Christian; Dösch, Andreas; Wangler, Susanne; Akhavanpoor, Mohammadreza; Ruhparwar, Arjang; Giannitsis, Evangelos; Katus, Hugo; Gleißner, Christian A. (Transplant international, 2013)
Following heart transplantation, cardiac biomarkers remain elevated for several weeks eventually as a result of membrane leakage of the donor organ. We now test the predictive power of blood levels of troponin T (TNT) measured by the new hsTNT assay (Roche Diagnostics, Roche Diagnostics, Mannheim, Germany) early after heart transplantation. TNT was determined in 141 cardiac allograft recipients and 40 controls. Our findings demonstrate that patients who died within the first year after transplantation had significantly higher median hsTNT serum levels 6 weeks after transplantation (156 ng/l ± 203 vs. 29 ng/l ± 21, P = 0.0002). Using ROC analysis, a serum hsTNT concentration of 33.55 ng/l 6 weeks after transplantation was found to be the best cutoff to predict death at 1 year (HR 0.16, 95%CI:0.05-0.46, P = 0.001) with a sensitivity of 90.91% and a specificity of 70.97%. In addition, survival at 5 years (HR 0.15, 95% CI 0.06-0.35, P < 0.0001) was significantly better among patients below that cutoff value. In multivariate analysis, hsTNT serum level 6 weeks after transplantation emerged as an independent predictor for first-year mortality (hsTNT-HR 0.90, 95% CI: 0.81-1.00, P = 0.03). Cardiac troponin T concentrations early after transplantation as measured with a highly sensitive assay represent a strong and independent risk predictor of death after heart transplantation.